PROSPEK USAHA PEMBUATAN CINCAU HITAM DI DESA TUGU HARUM BELITANG MADANG RAYA OKU TIMUR - Muridin Muridin (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2017)
Grass jelly is a traditional food items that have long been known to the public and used as a fill refreshment. Cincau disliked because distinctive taste, fresh and cold, and it's cheap., Black grass jelly beneficial to health, these properties are closely linked to the content of soluble fiber (soluble dietary fiber) contained therein. In the body, soluble fiber can bind sugar and fat / cholesterol, making it useful for preventing diabetes mellitus, heart disease, stroke, and other cardiovascular diseases.Black grass jelly contains a number of minerals and carbohydrates, vitamins A, B1, C, low in calories and has efficacy lowering body heat, the heat inside, preventing digestive disorders, high blood pressure and weight. Black grass jelly-making business actors in Desa Tugu Harum Belitang Madang subdistrict Kingdom East OKU District has been using the technique of making black grass jelly is good and right that start of boiling, filtering, heating, drilling and printing to marketing processes.Costs of production in one process of making black grass jelly in Desa Tugu Harum, District Belitang Madang Kingdom, East OKU district is Rp. 793,816.67 / production process. With a total production of 30 boxes and the selling price of Rp. 40,000 / box so as to obtain acceptance of Rp. 1.200.000 / production. While income earned in one process of making black grass jelly is Rp. 406,183.33.